Warfare, religion, and society in Indian history - Aquil, Raziuddin; Roy, Kaushik (New Delhi : Manohar Publishers & Distributors, 2012)
Contributed articles.
Includes bibliographical references (p. [315]-332) and index.
Keywords: War -- Religious aspects; India -- History, Military